Analysis Of Heart Disease Using Machine Learning Techniques (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
There is a very large number in the health sector and special methods are also used systematically. Data exchange is one of the most commonly used methods. Heart disease is one of the leading causes of death in the world. This system predicts the possibility of heart disease. The results of this system provide a 100% risk of heart disease. The data used are categorized according to medical criteria. The system evaluates these parameters using data extraction methods used in Python using two basic machine learning algorithms, the Solution Tree Algorithm, and the algorithm that demonstrates the best accuracy in heart disease.